Perspectives and Attitudes on the Credibility of News on Social Networking (SNSS) Sites: Urgent Need of Research Work - Safori, Amjad Omar; Rahman, Nik Adzrieman Abdul; Mohammed, Rosli (Journal of New Media and Mass Communication, 2016)
The role of journalists, and journalism has progressed into a more digitalized journalism. Social Networking Sites (SNSs) allow people to take part in online activities and remove the barrier for online users to publish and share information at any place at any time. Among various social media, this review limits its review scope to SNSs, which have been considered to be the most pertinent social medium used in the field of communication management. This paper intends to show that credibility of social media is the key factor that enhances public engagement and communication effectiveness in the digital/social media. This paper is intended to elicit the factors that could affect the credibility of news from SNSs. Specifically, this article reviews on the needs to study journalist perspectives and attitudes on the credibility of news published on SNSs sites, and found few variables that could affect the credibility of the media and the news, which is linked to journalistic work. These include: the interactive media, technology acceptance, quality of news’ source, and the exposure of the media. The review of the literature suggests the dire research needs to focus on journalists’ perspectives and attitudes towards the new media to ensure credibility of news and journalism is continuously sustained and improved.